2019
DOI: 10.1371/journal.pone.0214794
|View full text |Cite
|
Sign up to set email alerts
|

Rhodnius prolixus: Identification of missing components of the IMD immune signaling pathway and functional characterization of its role in eliminating bacteria

Abstract: The innate immune system in insects is regulated by specific signalling pathways. Most immune related pathways were identified and characterized in holometabolous insects such as Drosophila melanogaster , and it was assumed they would be highly conserved in all insects. The hemimetabolous insect, Rhodnius prolixus , has served as a model to study basic insect physiology, but also is a major vector of the human parasite, Trypanosoma cruzi , th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
3
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 92 publications
0
59
3
2
Order By: Relevance
“…prolixus genome was published [ 16 ]. However, recently, Salcedo-Porras et al [ 169 ] found orthologues for most of the “missing” elements of the IMD pathway in R . prolixus and reported that these are regulated in response to infection with Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…prolixus genome was published [ 16 ]. However, recently, Salcedo-Porras et al [ 169 ] found orthologues for most of the “missing” elements of the IMD pathway in R . prolixus and reported that these are regulated in response to infection with Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of IMD is not necessarily unusual, as it has also not been found in the pea aphid, A. pisum; the body louse, Pediculus humanus corporis; or the deer tick, Ixodes scapularis. Indeed, recent evidence suggests IMD is absent among hempiterans [116,117], although its absence indicates an as-yet-uncharacterized means for transducing a PGRPinitiated signal in response to bacterial challenge.…”
Section: Insect Immunitymentioning
confidence: 99%
“…The lack of an intact IMD pathway in psyllids and aphids has been suggested to relate to their obligate symbiotic associations [ 31 , 32 ]; however, this hypothesis does not explain the apparent lack of intact IMD pathway in phylloxera, which lacks obligate symbionts. We however note the possibility of divergent genes that would represent a functional pathway as recently shown fo r R. prolixus [ 33 ].…”
Section: Resultsmentioning
confidence: 98%